Food waste treatment methods and its effects on the growth quality of plants: a review - Arumugam, Veknesh; Ismail, Muhammad Heikal; Puspadaran, Tharsini Amma; Routray, Winny; Ngadisih, Ngadisih; Karyadi, Joko Nugroho Wahyu; Suwignyo, Bambang; Suryatmojo, Hatma (Universiti Putra Malaysia Press, 2022)
Food waste and leftovers were common materials that were currently used as biocompost or soil conditioners upon decomposition. Food waste was a source of food that has declined nutritional value and is not deemed favorable for human consumption. Leftovers were defined as uneaten edible remains of a meal. Biodegradation of these components contributes to many macronutrients, including carbon (C), hydrogen (H), nitrogen (N), phosphorus (P), and potassium (K) in the compost, which makes it a suitable growing condition for plants. In this study, the main sources of research data were one hundred thirty-one scientific articles relating to food waste treatment methods and the growth quality of plants over the last few years. This review was the consensus of the role and characteristics of food waste and leftovers as fertilizers. Moreover, the paper briefly discusses the different composting methods for these materials and their corresponding effects on the growth quality of plants.